2024
DOI: 10.1111/jerd.13235
|View full text |Cite
|
Sign up to set email alerts
|

Immediate loading on two adjacent single dental implants with definitive nonsplinted restorations: A proof of concept in the posterior zone

Jin‐Young Park,
Franz‐Josef Strauss,
Lucia Schiavon
et al.

Abstract: ObjectivesTo evaluate clinical, clinician‐ and patient‐reported outcomes (PROs) of two adjacent single posterior implants immediately loaded with definitive single crowns up to 1 year. Ten patients in need of two adjacent posterior single implants were included. All implants were placed applying a fully digital workflow. Definitive screw‐retained single zirconia crowns were delivered within 72 h after implant placement. Clinical parameters, patient‐ and clinician‐reported outcomes were assessed up to 1 year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Cone-beam computed tomography with pre-surgical planning caused more ancillary procedures to be performed during implant placement surgery [13,14]. Early implant placement with simultaneous contour augmentation using CBCT in a study performed by Dannie Buser, et al (2013) [60] demonstrated stable peri-implant hard and soft tissues for all 41 implants examined and satisfactory aesthetic outcomes overall [10,61]. Follow-up at 5 to 9 years confirmed again that the risk of mucosal recession was low with early implant placement [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cone-beam computed tomography with pre-surgical planning caused more ancillary procedures to be performed during implant placement surgery [13,14]. Early implant placement with simultaneous contour augmentation using CBCT in a study performed by Dannie Buser, et al (2013) [60] demonstrated stable peri-implant hard and soft tissues for all 41 implants examined and satisfactory aesthetic outcomes overall [10,61]. Follow-up at 5 to 9 years confirmed again that the risk of mucosal recession was low with early implant placement [62].…”
Section: Discussionmentioning
confidence: 99%
“…All these studies investigated bone density in relation to outcome when implants were placed according to standard protocol [9]. The results of these studies show that the early loading of implants utilizing a flapless surgical technique with CT-guided surgical stents may be possible [10]. In 1985, Misch and Judy established four basic divisions of available bone for implant dentistry in the maxilla and mandible, which also follows the natural resorption phenomena [11].…”
Section: Introductionmentioning
confidence: 99%